Perceptions of hospital pharmacists regarding roles in preventing and minimizing prescribing cascades: a mixed-method study - Mahnoor Asad; Waseem Ullah; Márió Gajdács; Melinda Madléna; Suresh Shanmugham; Sajesh K Veettil; Shazia Q Jamshed (Journal of Infection in Developing Countries)
Introduction: A prescribing cascade occurs when new medications are prescribed to address an adverse drug reaction (ADR) associated with the preceding use of a medication, which may be mistaken as the onset of a novel disease or condition. The aim of this study was to evaluate the perceptions of hospital pharmacists regarding roles in preventing and minimizing prescribing cascades.